SMOKING MAY BE RELATED TO SACROILIITIS IN ENTEROPATHIC ARTHRITIS PATIENTS: TREASURE REAL-LIFE PRELIMINARY DATA - Kucuksahin, Orhan; Erden, Abdulsamet; Ilgen, Ufuk; Kiraz, Sedat; Ertenli, Ali Ihsan; Bilge, Nazife Sule Yasar; Kalyoncu, Umut (Bmj Publishing Group, 2019)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 12-15, 2019 -- Madrid, SPAIN